2019
DOI: 10.21608/jappmu.2019.71358
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Nutritive Value of Watermelon Vines and Its Effect on Productive Performance of Growing Lambs

Abstract: This experiment was conducted to study the effect of using biological treatment by (Trichoderma reesei), to reduce the content of antinutritional factors in watermelon vines and improvement their nutritive value and the possibility of using it in animal nutrition and its effect on productive performance of growing lambs. Fifty male Barki lambs at 6 to 8 months of age with an average live body weight 24.49 ±0.2 Kg were divided into five similar groups according to their live body weight (10 lambs for each). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Such slightly increases of TVFA´s concentration may be due the effects of DM digestibility, rate of absorption, rumen pH and microbial population in the rumen and their activities (Allam et al, 1984). The obtained results are in agreement with those recorded by Fayed et al (2019a) who showed that rumen liquor pH values did not significantly differ among treatments, while contrariwise, NH3-N and TVFA's concentrations were significantly (P < 0.05) decreases with increasing the level of watermelon vines hay up to 100% replacement of berseem hay in ration of sheep. Ultimately, the progress made in the representation and quantification of the rumen fermentation process in models stimulating whole rumen function has been significant, although important gaps in knowledge and representation still remain.…”
Section: Rumen Fermentationsupporting
confidence: 91%
See 3 more Smart Citations
“…Such slightly increases of TVFA´s concentration may be due the effects of DM digestibility, rate of absorption, rumen pH and microbial population in the rumen and their activities (Allam et al, 1984). The obtained results are in agreement with those recorded by Fayed et al (2019a) who showed that rumen liquor pH values did not significantly differ among treatments, while contrariwise, NH3-N and TVFA's concentrations were significantly (P < 0.05) decreases with increasing the level of watermelon vines hay up to 100% replacement of berseem hay in ration of sheep. Ultimately, the progress made in the representation and quantification of the rumen fermentation process in models stimulating whole rumen function has been significant, although important gaps in knowledge and representation still remain.…”
Section: Rumen Fermentationsupporting
confidence: 91%
“…The obtained results are in agreement with the findings obtained by Hussien (2009) who reported that digestibility of most nutrients of DM, OM, CP, CF, EE, NFE and feeding values were significantly decreased with including the cantaloupe and squash vines in diets of rabbits compared with clover hay. Also, the same trends were found by Fayed et al (2019a) who reported that digestibility of most nutrients were significantly decreased with increasing the level of dried watermelon vines in rations of growing lambs. Likewise, Soliman et al (2020) found that digestibility of most nutrients were improved with cows fed rations containing 25 and 50 % watermelon vines, while those animals fed rations of higher levels of watermelon vines (75 and 100%) were recorded the lowest values (P<0.05).…”
Section: Nutrients Digestibilties and Feeding Valuessupporting
confidence: 83%
See 2 more Smart Citations